2008
DOI: 10.1038/nature06494
|View full text |Cite
|
Sign up to set email alerts
|

Identification of RPS14 as a 5q- syndrome gene by RNA interference screen

Abstract: Somatic chromosomal deletions in cancer are thought to indicate the location of tumor suppressor genes, whereby complete loss of gene function occurs through biallelic deletion, point mutation, or epigenetic silencing, thus fulfilling Knudson's two-hit hypothesis.1 In many recurrent deletions, however, such biallelic inactivation has not been found. One prominent example is the 5q- syndrome, a subtype of myelodysplastic syndrome (MDS) characterized by a defect in erythroid differentiation.2 Here, we describe a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

15
678
4
6

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 827 publications
(706 citation statements)
references
References 29 publications
15
678
4
6
Order By: Relevance
“…Several other hematopoiesis-related genes and tumor suppressor genes are located in the CDR (e.g., CTNNA1, PPP2CA, EGR1, SPARC, RPS14 and CDC25C) with previously reported [14,[27][28][29][30][31], however, we were unable to detect hemi-or heterozygous mutations in Oncotarget 6491 www.impactjournals.com/oncotarget these genes. It is possible that they contribute to clinical heterogeneity, shape the clinical phenotype or modulate the growth advantage of the del(5q).…”
Section: Figure 3: Presence Of Coexisting Genetic Events With Del(5q)contrasting
confidence: 79%
“…Several other hematopoiesis-related genes and tumor suppressor genes are located in the CDR (e.g., CTNNA1, PPP2CA, EGR1, SPARC, RPS14 and CDC25C) with previously reported [14,[27][28][29][30][31], however, we were unable to detect hemi-or heterozygous mutations in Oncotarget 6491 www.impactjournals.com/oncotarget these genes. It is possible that they contribute to clinical heterogeneity, shape the clinical phenotype or modulate the growth advantage of the del(5q).…”
Section: Figure 3: Presence Of Coexisting Genetic Events With Del(5q)contrasting
confidence: 79%
“…The RPS14 gene, encoding a ribosomal protein and mapping to the commonly deleted region (CDR) of the 5q-syndrome, 1 shows haploinsufficiency in the CD34 ĂŸ cells of patients with this disorder. 2,3 The genes in the 5q-syndrome CDR were studied by an RNA-mediated interference-based approach and it was shown that haploinsufficiency of RPS14 in normal CD34 ĂŸ cells resulted in a block in erythroid differentiation with relative preservation of megakaryocyte differentiation, suggesting that RPS14 haploinsufficiency is the probable cause of the erythroid defect in this disorder. 3 Several lines of converging evidence suggest that p53 activation secondary to ribosomal haploinsufficiency is the mechanism that underlies the anemia in the 5q-syndrome.…”
mentioning
confidence: 99%
“…2,3 The genes in the 5q-syndrome CDR were studied by an RNA-mediated interference-based approach and it was shown that haploinsufficiency of RPS14 in normal CD34 ĂŸ cells resulted in a block in erythroid differentiation with relative preservation of megakaryocyte differentiation, suggesting that RPS14 haploinsufficiency is the probable cause of the erythroid defect in this disorder. 3 Several lines of converging evidence suggest that p53 activation secondary to ribosomal haploinsufficiency is the mechanism that underlies the anemia in the 5q-syndrome. 4,5 The bone marrow cells of patients with the 5q-syndrome show a block in the processing of pre-ribosomal RNA 3 and the CD34 ĂŸ cells of these patients show deregulation of multiple ribosomal protein genes and genes involved in the control of translation.…”
mentioning
confidence: 99%
See 2 more Smart Citations